CXCR5+PD-1+ follicular helper CD8 T cells control B cell tolerance - Yuhong Chen (Nature Portfolio, 2019)
B cell response and antibody production are generally facilitated by CD4+ follicular helper (Tfh) cells. Here the authors identify a subset of CXCR5+PD1+CD8+ Tfh cells that is normally suppressed by STAT5 signaling, so that STAT5 deficiency in mice increases the number of these CD8+ Tfh cells and induces concomitant production of autoantibodies.